The post-war situation and tourism in Syunik - Hovsepyan, Ruben (History and Culture, 2025)
Tourism is one of the most important factors of economic development in many countries. Its role is very important in the development of small towns and rural communities, contributing not only to economic revitalization, but also to the cultural life of communities. The role of tourism is also important in the life of border settlements.This article examines the changes in the tourism industry of the Syunik region of the Republic of Armenia as a result of the 44-day war in 2020 and the attack by Azerbaijan on the borders of the Republic of Armenia in 2021 and 2022.As a result of the military operations carried out by Azerbaijan and the border tension in the last four years, the tourism sector of Syunik underwent negative changes. Many communities of the region became border, many historical, cultural and natural monuments and specially protected zones appeared very close to the border. Security problems developed around the region, which significantly affected the tourist inflow.In the Syunik region, the idea of ​​a conflict border, a border zone is prominent when warring, conflicting parties try to influence the other border section by various means, including military actions. This not only affects economic activity, but also risks creating negative perceptions around the border zone and, as a consequence, alienation.One of the primary factors in the development of tourism is the concept of security, on the other hand, tourism is active in many conflict and border zones with security problems. As an example, we can consider Israel, the border zone between China and India, etc.
Keywords: border; Syunik; tourism; war and conflict